2021
DOI: 10.1002/jha2.311
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma treatment options for elderly/unfit patients: A systematic review

Abstract: Mantle cell lymphoma (MCL) is a rare B-cell non-Hodgkin lymphoma (NHL) that is aggressive and incurable with existing therapies, presenting a significant unmet clinical need. MCL occurs mainly in elderly patients with comorbidities; thus, intense treatment options including allogeneic stem cell transplantation (Allo-SCT) are not feasible.New treatment options are emerging for this elderly/unfit treatment group, we therefore conducted a systematic review to determine whether they offered an advance on the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Drug resistance in the treatment of MCL with ibrutinib may also be a factor. 34,35 Our results suggested that VR-CAP regimen (SUCRA 0.89, PbBT 63%) may be the most effective treatment regimen for prolonged OS in MCL patients. This treatment strategy was to replace vincristine with bortezomib on the basis of R-CHOP regimen.…”
Section: Discussionmentioning
confidence: 75%
“…Drug resistance in the treatment of MCL with ibrutinib may also be a factor. 34,35 Our results suggested that VR-CAP regimen (SUCRA 0.89, PbBT 63%) may be the most effective treatment regimen for prolonged OS in MCL patients. This treatment strategy was to replace vincristine with bortezomib on the basis of R-CHOP regimen.…”
Section: Discussionmentioning
confidence: 75%
“…Research continues, focused particularly on relapsed and high-risk patients. There are different treatment options for younger patients without comorbidities and for elderly fit patients [ 32 ]. High-dose therapy and autologous stem-cell rescue and high-dose cytarabine in younger patients has shown benefits, as has maintenance rituximab and bendamustine in older patients.…”
Section: Situation Reportmentioning
confidence: 99%
“…MCL is an aggressive B-cell non-Hodgkin's lymphoma (B-NHL) which is incurable with current treatment options, and overall survival (OS) ranges between 3 and 5 years [1][2][3][4] . MCL is genetically characterised by the t11;14 translocation which results in overexpression of cyclin D1.…”
mentioning
confidence: 99%
“…MCL is genetically characterised by the t11;14 translocation which results in overexpression of cyclin D1. Although the translocation and consequence overexpression of cyclin D1 is not sufficient to induce lymphomagenesis it probably facilitates the process by deregulating the cell cycle [1][2][3][4] . It has been long been known that MCL has two distinct clinical entities described as classical (nodal) MCL, and a leukaemic (non-nodal) variant.…”
mentioning
confidence: 99%
See 1 more Smart Citation